Scanning electron microscopy imaging mechanisms of CVD-grown graphene on Cu substrate revealed by in situ observation. (2nd April 2015) - Wang, Huafeng; Yamada, Chisato; Homma, Yoshikazu
Abstract: We performed in situ scanning electron microscopy (SEM) observation of the image contrast changes induced by vacuum heating of chemical-vapor-deposition-grown graphene on a Cu substrate. We demonstrated that the graphene on a pure Cu surface is invisible to SEM observation. Air exposure leads to the SEM contrast of graphene on Cu, which originates not only from uncovered Cu surface areas at the boundaries of graphene domains but also from graphene covered regions. This may be due to the adsorbed gases on the uncovered Cu surface and the formation of an intercalated gas layer between graphene and the Cu substrate.